CCAFS science supports new Rainforest Alliance projects in Honduras, Indonesia, Ivory Coast and beyond - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
CCAFS science and approaches changed Rainforest Alliance practices leading to new projects in Honduras, Indonesia, Cote d'Ivoire and globally reaching more than 28,000 producers. Specifically Rainforest Alliance adopted the application and of the risk assessment of climate impacts and the identification and development of CSA recommendations for both coffee and cocoa to achieve scaling out.